2013
DOI: 10.1007/s11596-013-1075-1
|View full text |Cite
|
Sign up to set email alerts
|

Close correlation between development of MODS during the initial 72 h of hospitalization and hospital mortality in severe fever with thrombocytopenia syndrome

Abstract: An emerging infectious disease was identified as severe fever with thrombocytopenia syndrome (SFTS) in central China since late March 2009. We found the patients with SFTS had severe clinical symptoms, and progressed rapidly to multiple organ dysfunction syndrome (MODS) with high fatality rate of 25%-30%. The aim of this study was to assess the significance of risk factors predicting the development of MODS and death in SFTS patients. Consecutive SFTS admissions between May 2009 and September 2011 were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Dynamic specimen collection (more than twice per patient) was performed in 15 of the 30 patients enrolled. The demographic data showed that the average age of severe cases was slightly higher than that of non-severe cases, and we have confirmed that advanced age was one of the main risk factors for the development of MODS and death [6]. Platelet counts in patients with severe disease were lower than in those with non-severe disease ( Table I).…”
Section: General Characteristics Of Patients With Sftssupporting
confidence: 66%
See 1 more Smart Citation
“…Dynamic specimen collection (more than twice per patient) was performed in 15 of the 30 patients enrolled. The demographic data showed that the average age of severe cases was slightly higher than that of non-severe cases, and we have confirmed that advanced age was one of the main risk factors for the development of MODS and death [6]. Platelet counts in patients with severe disease were lower than in those with non-severe disease ( Table I).…”
Section: General Characteristics Of Patients With Sftssupporting
confidence: 66%
“…The condition of some patients with severe SFTS deteriorates rapidly and quickly proceeds to multiple organ dysfunction syndrome (MODS), even ending with multi-organ failure (MOF) and death [3]. Studies have shown that the occurrence of MODS during initial hospitalization within 72 h is closely associated with mortality [6]. authors have found that SFTS is associated with host immune response, which plays a critical role in determining the severity and clinical outcome of patients who are infected by SFTSV [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SFTS have severe clinical symptoms, and progress rapidly to multiple organ dysfunction syndrome (MODS), with a high fatality rate of 12%-30% [3]. Multiorgan failure is associated with death and the SFTS patients with MODS who died were older and had lower platelet counts than those who survived [28]. Mortality was significantly higher in misdiagnosed SFTS patients than in patients with confirmed SFTS (16% vs. 6.1%, respectively) [28].…”
Section: Clinical Symptoms and Diagnosis Of Sftsmentioning
confidence: 99%
“…Multiorgan failure is associated with death and the SFTS patients with MODS who died were older and had lower platelet counts than those who survived [28]. Mortality was significantly higher in misdiagnosed SFTS patients than in patients with confirmed SFTS (16% vs. 6.1%, respectively) [28]. The treatment for SFTS is nonspecific and the results of treatment are difficult to evaluate because there have been no cohort studies.…”
Section: Clinical Symptoms and Diagnosis Of Sftsmentioning
confidence: 99%
“…The hemophagocytic macrophages will further decrease the cell number in the three cell lines. Patients with SFTS will have significantly decreased blood platelet counts and tend to suffer from multiorgan failure, which eventually leads to death [8].…”
Section: Discussionmentioning
confidence: 99%